2003
DOI: 10.1523/jneurosci.23-28-09395.2003
|View full text |Cite
|
Sign up to set email alerts
|

Hyperdopaminergic Mutant Mice Have Higher “Wanting” But Not “Liking” for Sweet Rewards

Abstract: What is the role of dopamine in natural rewards? A genetic mutant approach was taken to examine the consequences of elevated synaptic dopamine on (1) spontaneous food and water intake, (2) incentive motivation and learning to obtain a palatable sweet reward in a runway task, and (3) affective "liking" reactions elicited by the taste of sucrose. A dopamine transporter (DAT) knockdown mutation that preserves only 10% of normal DAT, and therefore causes mutant mice to have 70% elevated levels of synaptic dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
300
4
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 468 publications
(332 citation statements)
references
References 65 publications
(92 reference statements)
26
300
4
2
Order By: Relevance
“…As previously reported, mice showed strong positive taste reactions to intraoral infusion of sucrose ( Figure 1) and extensive negative taste reactions to quinine (Figure 2) [39,43]. There were no significant interactions between testing session and treatment group or differences between vehicle and nicotine treated subjects in any taste reactions throughout chronic nicotine treatment and spontaneous withdrawal.…”
Section: Experiments 1: Measurement Of Taste Reactions During Chronic supporting
confidence: 80%
See 1 more Smart Citation
“…As previously reported, mice showed strong positive taste reactions to intraoral infusion of sucrose ( Figure 1) and extensive negative taste reactions to quinine (Figure 2) [39,43]. There were no significant interactions between testing session and treatment group or differences between vehicle and nicotine treated subjects in any taste reactions throughout chronic nicotine treatment and spontaneous withdrawal.…”
Section: Experiments 1: Measurement Of Taste Reactions During Chronic supporting
confidence: 80%
“…Behavioral reactions were classified as positive, aversive and neutral according to previous studies in mice [39,43]. Positive hedonic reactions included rhythmic tongue protrusions, single tongue protrusions, and paw licking.…”
Section: Analysis Of Taste Reactionsmentioning
confidence: 99%
“…One line of evidence against a pleasure-causing role is that mesolimbic dopamine neurons may not reliably be activated by pleasure per se but instead by predictive, motivational, or attentional properties rather than hedonic properties of reward stimuli (Carelli 2004;Cheer et al 2007;Redgrave and Gurney 2006;Salamone et al 2007;Schultz et al 1997). Another line of evidence is that, when 'liking' versus 'wanting' are teased apart by brain manipulations, specific manipulation of dopamine signaling either up or down simply fail to shift 'liking' reactions to pleasure reliably in either animals or humans (Berridge 2007;Brauer and De Wit 1997;Cannon and Palmiter 2003;Evans et al 2006;Leyton 2008;Leyton et al 2002;Leyton et al 2005;Peciña et al 2003;Robinson et al 2005;Tindell et al 2005;Volkow et al 2002;Volkow et al 2006). A third line of evidence is that dopamine systems may also be activated by aversive or frankly non-rewarding stimuli, at least tonic dopamine release pulses that last on the order of a few minutes (Ferrari et al 2003;Horvitz 2000;Salamone 1994;Scott et al 2006).…”
Section: Controversial Subcortical Pleasure Generators? Dopamine and mentioning
confidence: 99%
“…Defined as a want for something you neither like nor expect to like, strongly irrational desire may be rare but does exist (the electrode cases above might be examples). In animal experiments, irrational 'wanting' has been suggested to be created through activation of brain dopamine-related systems via systemic or intra-accumbens amphetamine administration and by psychostimulant-induced neural sensitization of accumbens-related systems (Flagel et al 2007;Peciña et al 2003;Tindell et al 2005;Uslaner et al 2006;Vezina 2004;Wyvell and Berridge 2001). In humans, drug-induced irrational 'wanting' has been suggested to occur via incentive sensitization in some drug addicts, which may create a motivational compulsion to take drugs again even if a drug is not particularly pleasant and even after recovery from withdrawal (Robinson and Berridge 1993;Robinson and Berridge 2003).…”
Section: Dopamine-beyond Learning Too?mentioning
confidence: 99%
“…According to this theory, the pursuit of a reward is not always directly proportional to the pleasure experienced, because reward processing involves distinct components, including the motivation to obtain a reward (i.e., wanting) and the hedonic pleasure during the reward consumption (i.e., liking), which are usually correlated but can be dissociated under particular circumstances. Experiments conducted on rodents showed that direct manipulation of mesolimbic dopamine increases effort mobilization after the presentation of a reward-associated cue (i.e., wanting), without simultaneously increasing hedonic pleasure (i.e., liking) during reward consumption (Peciña, Cagniard, Berridge, Aldridge, & Zhuang, 2003; 6 1 Wyvell & Berridge, 2000). This supports the idea that wanting and liking rely on two distinct neuronal networks that can be activated independently of each other (Berridge & Robinson, 1998).…”
Section: Appendixmentioning
confidence: 99%